Nise da Silveira, Fernando Diniz e Leon Hirszman: politics, society and arts (Psicologia USP, 2010)
This article talks about the construction process of the movie Imagens do Inconsciente, more specifically about the episode Em Busca do Espaço Cotidiano, about Fernando Diniz and his pictorial production. The meeting between the psychiatrist Nise da Silveira and the film maker Leon Hirszman is marked by the non-dissociation of politics, society and arts. The therapeutic and the psychosocial rehabilitation work developed by Nise da Silveira has as characteristic the establishment of important connections to the arts field, making possible the dialogue with all the society. This cultural and mentalities transformation work made the social exclusion of the called mental sick be questioned and transformed the help policy in the mental health field in Brazil.